2021
DOI: 10.1101/2021.03.11.21253347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study identifies two new loci associated with anti-NMDAR encephalitis

Abstract: Objective: To investigate the genetic determinants of the most common type of antibody-mediated autoimmune encephalitis, anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. Methods: We performed a genome-wide association study in 178 patients with anti-NMDAR encephalitis and 590 healthy controls followed by a colocalization analysis to identify putatively causal genes. Results: We identified two independent risk loci harboring genome-wide significant variants (P < 5 x 10-8, OR ≥ 2.2), one on chrom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Genetic susceptibility variants for NMDAR-encephalitis have only recently been described, with one gene also being under debate in multiple sclerosis. 44,45 In our case, the morphology of the demyelinating lesions was consistent with classic MS with periventricular, plaque-like demyelination with radially expanding lesions, and signs of remyelination with shadow plaques. The absence of complement deposition in the demyelinating lesions may indicate other inflammatory mechanisms, such as microglia-driven tissue injury.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Genetic susceptibility variants for NMDAR-encephalitis have only recently been described, with one gene also being under debate in multiple sclerosis. 44,45 In our case, the morphology of the demyelinating lesions was consistent with classic MS with periventricular, plaque-like demyelination with radially expanding lesions, and signs of remyelination with shadow plaques. The absence of complement deposition in the demyelinating lesions may indicate other inflammatory mechanisms, such as microglia-driven tissue injury.…”
Section: Discussionsupporting
confidence: 72%
“…In cases with concomitant MOG‐ or AQP4‐antibodies, a genetic susceptibility towards humoral autoimmunity may play a role. Genetic susceptibility variants for NMDAR‐encephalitis have only recently been described, with one gene also being under debate in multiple sclerosis 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to further validate our study, whole-genome sequencing would be an additional tool to investigate intronic variations near splicing sites, patterns similar to those observed in tumors associated with anti-Yo antibodies. 22 Considering that a genome-wide study suggested candidate peripheral blood genes associated with B cell development, 23 it is also important to identify other immune cell-intrinsic etiologies from peripheral blood. In contrast to leucinerich glioma inactivated1-antibody encephalitis, 24,25 NMDARe has no specific human leukocyte antigen (HLA) subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the patients with NMDARe and the controls was 23.9 AE 6.4 (range: 17-37) and 24.4 AE 6.2 , respectively. The patients with NMDARe had a poor initial clinical profile showing a median NEOS score of 3 (interquartile range: 2-4), a median CASE score of 22 (19)(20)(21)(22)(23), and a median mRS score of 5 [5]. The mean duration from symptom onset to teratoma removal was 60.6 AE 83.0 days (ranged from 10 to 300).…”
Section: Clinical Characteristics Of Patientsmentioning
confidence: 99%
“…11 An underlying immunogenetic predisposition to paraneoplastic neurologic disorders may be present, as seen with human leukocyte antigen-type and immune gene associations for NMDA-receptor encephalitis. 12 This is most suggestive in syndromes with a low incidence of associated tumors: 90% of patients with IgLON family member 5 (IgLON5)-related syndromes have the DQB1*05 allele and 60% also have the DRB1*10:01 allele; 90% of patients with contactin-associated proteinlike 2 (CASPR2)-related syndromes have the DRB1*11:01 allele; and 40% of patients with glutamic acid decarboxylase 65 (GAD65)-related syndromes have the DQB*02:01 allele. However, no genetic human leukocyte antigen-type associations were found for anti-Purkinje cell cytoplasmic antibody type 1 (PCA-1) (Yo) antibodies and other paraneoplastic syndromes with a high…”
Section: Clinical Evaluation Of Paraneoplastic Disordersmentioning
confidence: 99%